The Fundamentals of Institutional Communications: an historical and conceptualapproach of the profession - Rodrich Portugal, Rolando (2022)
The following paper presents an historical approach of the Corporate Communications origins, to develop perspectives on their roles in the organization, strengths, weaknesses and, above all, to fully understand the role and place of its social purpose.To this end, the focus is on the concept study of the Corporate Communication. The knowledge and academic research on the discipline is also a reflection of a profession enhanced by the diversity of management areas and encouraging their continued development and innovation, generating that professionals need to keep up, know what happens in other markets and countries, and study the main theoretical advances that offer perspectives and promote quality.